2021
DOI: 10.3389/fncel.2021.629356
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin-3 Promotes the Neuronal Differentiation of BMSCs and Improves Cognitive Function in a Rat Model of Alzheimer's Disease

Abstract: Transplantation of bone marrow-derived mesenchymal stem cells (BMSCs) has the potential to be developed into an effective treatment for neurodegenerative diseases such as Alzheimer's disease (AD). However, the therapeutic effects of BMSCs are limited by their low neural differentiation rate. We transfected BMSCs with neurotrophin-3 (NT-3), a neurotrophic factor that promotes neuronal differentiation, and investigated the effects of NT-3 gene overexpression on the differentiation of BMSCs into neurons in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…MSCs, on the other hand, are capable of multidirectional differentiation and can be a good source of cells for disc degeneration repair ( Brown et al, 2019 ; Clouet et al, 2019 ). In this study, we isolated MSCs from rat bone marrow tissues, and the isolated cells had the following characteristics: 1) the isolated cells became spindle-shaped against the wall and could form cell colonies; 2) high expression of CD105 and CD90 (>95%), and low expression of CD34 and CD45 (<5%) ( Pham et al, 2018 ; Tian et al, 2019 ; Yan et al, 2021 ). It was also demonstrated that MSCs of bone marrow origin could differentiate toward cartilage via differentiation ability verification, and a previous study also demonstrated that MSCs could differentiate toward myeloid cells under the influence of a myeloid conditioned media environment, which could be applied to the repair of degenerated discs ( Sinkemani et al, 2020 ; Felka et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs, on the other hand, are capable of multidirectional differentiation and can be a good source of cells for disc degeneration repair ( Brown et al, 2019 ; Clouet et al, 2019 ). In this study, we isolated MSCs from rat bone marrow tissues, and the isolated cells had the following characteristics: 1) the isolated cells became spindle-shaped against the wall and could form cell colonies; 2) high expression of CD105 and CD90 (>95%), and low expression of CD34 and CD45 (<5%) ( Pham et al, 2018 ; Tian et al, 2019 ; Yan et al, 2021 ). It was also demonstrated that MSCs of bone marrow origin could differentiate toward cartilage via differentiation ability verification, and a previous study also demonstrated that MSCs could differentiate toward myeloid cells under the influence of a myeloid conditioned media environment, which could be applied to the repair of degenerated discs ( Sinkemani et al, 2020 ; Felka et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, human UC-MSCs cocultured with activated astrocytes and then seeded on RADA16-BDNF-loaded self-assembling peptide hydrogel (R-B-SPH) differentiated into neuron-like cells with neurites extending in three-dimensional directions, which may benefit both the neural differentiation of ectogenic UC-MSCs and endogenic neurogenesis in a rat TBI model [ 157 ], suggesting potential therapeutic utility for reconstructing damaged neuronal circuits. Also, the overexpression of NT-3 promoted the neuronal differentiation of BMSCs and improved cognitive function in Alzheimer's disease (AD) model rats [ 158 ]. BMSCs overexpressing SHH increased the expression and secretion of SHH, bFGF and VEGF, that benefit the survival and nervous behavioral function of BMSCs and significantly enhanced the recovery of neurological function after SCI in rats [ 159 ].…”
Section: Selecting Appropriate Genes For Transductionmentioning
confidence: 99%
“…Recent scientific evidence also indicates to a neuroprotective role for NT-3 in AD progression, including the study by Yan et al, in which NT-3 overexpression in AD rats was associated with improved cognitive function [ 94 ]. Specifically, transplantation of bone marrow-derived mesenchymal stem cells (BMSCs) overexpressing NT-3 was shown to promote neurorigeneration and cognitive gain in AD rats, pointing to β-catenin as a key candidate responsible for this effect.…”
Section: Physical Exercise As a Non-pharmacological Strategy To Preve...mentioning
confidence: 99%
“…However, translocation of β-catenin from the cytoplasm to the nucleus results in activation of downstream targets that ultimately promote cell survival and proliferation. The authors demonstrated that NT-3 can influence β-catenin expression, although the underlying mechanism remains unclear [ 94 ].…”
Section: Physical Exercise As a Non-pharmacological Strategy To Preve...mentioning
confidence: 99%